Effect of Exo/Endogenous Prophylaxis Dentifrice/Drug and Cariogenic Conditions of Patient on Molecular Property of Dental Biofilm: Synchrotron FTIR Spectroscopic Study - Pavel Seredin; Dmitry Goloshchapov; Vladimir Kashkarov; Dmitry Nesterov; Yuri Ippolitov; Ivan Ippolitov; Jitraporn Vongsvivut (MDPI AG, 2022)
(1) Objectives: This study is the first one to investigate the molecular composition of the dental biofilm during the exogenous and endogenous prophylaxis stages (use of dentifrice/drug) of individuals with different cariogenic conditions using molecular spectroscopy methods. (2) Materials and Methods: The study involved 100 participants (50 males and 50 females), aged 18-25 years with different caries conditions. Biofilm samples were collected from the teeth surface of all participants. The molecular composition of biofilms was investigated using synchrotron infrared microspectroscopy. Changes in the molecular composition were studied through calculation and analysis of ratios between organic and mineral components of biofilm samples. (3) Results: Based on the data obtained by synchrotron FTIR, calculations of organic and mineral component ratios, and statistical analysis of the data, we were able to assess changes occurring in the molecular composition of the dental biofilm. Variations in the phosphate/protein/lipid, phosphate/mineral, and phospholipid/lipid ratios and the presence of statistically significant intra- and inter-group differences in these ratios indicate that the mechanisms of ion adsorption, compounds and complexes arriving from oral fluid into dental biofilm during exo/endogenous prophylaxis, differ for patients in norm and caries development. (4) Conclusions: The conformational environment and charge interaction in the microbiota and the electrostatic state of the biofilm protein network in patients with different cariogenic conditions play an important role. (5) Clinical Significance: Understanding the changes that occur in the molecular composition of the dental biofilm in different oral homeostasis conditions will enable successful transition to a personalised approach in dentistry and high-tech healthcare.